Layanan bimbingan kelompok dalam meningkatkan komunikasi interpersonal siswa - Fijriani Fijriani; Rediska Amaliawati (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
The purpose of this research is to reveal the effectiveness of group guidance in improving student interpersonal communication at the X grade in SMAN 1 Tanjurhalang. This research used quantitative approach with quasi experimental by using pre-test post test control group design. The sample was taken by using purposive sampling technique. This research used 20 students as sample that was divided into two class, 10 students as experimental class and 10 students as control class. In the experimental class. Group guidance processed in 8 meetings. After conducting a series of research, finally the writer concluded that group counseling of guidance are effective in improving interpersonal communication at the X grade students of SMAN 1 Tanjurhalang.